Neglected no more: Achievements of the IFAD-NUS project (2001-2005)Framework for its follow-up initiative (2007-2009) - Bioversity International (2007)
In 2001, with financial backing from the International Fund for Agricultural Development (IFAD), Bioversity International started a programme called Enhancing the contribution of neglected and underutilized species to food security and to incomes of the rural poor. This programme was successfully completed four years later, laying the groundwork for a three-year follow-up programme, Empowering the rural poor by strengthening their identity, income opportunities and nutritional security through the improved use and marketing of neglected and underutilized species, which started in 2007. The foundation for these studies is a firmly held and increasingly recognized belief that biodiversity is important for people's lives, and that one way of protecting biodiversity is by supporting the use and appreciation of plant species that are currently neglected and underutilized. This publication reports some of the findings of the first study. Find out more about Neglected and Underutilized Species at: Neglected and Underutilized Species Global Facilitation Unit for Underutilized Species The International Center for Underutilised Crops